Protective Effect of Lemon Peel Polyphenols on Oxidative Stress-Induced Damage to Human Keratinocyte HaCaT Cells Through Activation of the Nrf2/HO-1 Signaling Pathway - Gao, Xi; Xu, Diru; Zhang, Xinyue; Zhao, Hengguang (Frontiers in Nutrition, 2021)
Lemon peel can be used as traditional Chinese medicine. Flavonoids are the most important components in lemon peel, which can be developed as natural medicine without side effects. This study investigated the protective effect of lemon peel polyphenols (LPP) on human keratinocyte HaCaT cells under oxidative stress. The active components of LPP were determined by high performance liquid chromatography. The abilities of LPP to scavenge DPPH and ABTS+ free radicals were studied for detection of antioxidation in vitro. Cell survival rates were determined by MTT assay. The antioxidant enzyme activity and antioxidant index of cells were determined using kit. The mRNA and protein expression of cells were determined by qPCR and western blot. The ability of LPP to scavenge DPPH and ABTS+ free radicals were stronger than those of vitamin C (Vc) at the same concentration. As expected, compared with the normal group of cells, the model group had decreased cell survival, increased lactate dehydrogenase (LDH), decreased levels of superoxide dismutase (SOD), catalase (CAT) and glutathione (GSH), and increased malondialdehyde (MDA) content. qPCR and western blot results indicated that the expression of Bcl-2-related X protein (Bax), caspases-3, erythroid-derived nuclear factor 2-related factor 2 (Nrf2), and heme oxygenase-1 (HO-1) were decreased and the expression of B-cell lymphoma-2 (Bcl-2) was increased in the model group, compared with the normal group. LPP treatment improved cell survival rate, reduced intracellular LDH and MDA levels, increased intracellular SOD, CAT, GSH levels, down-regulated Bax, caspases-3, Nrf2, HO-1 expression, and up-regulated Bcl-2 expression. Component analyses found that LPP contains gallic acid, neochlorogenic acid, (+)-catechin, caffeic acid, (-)-Catechin gallate, isochlorogenic acid A, rosmarinic acid, and protocatechuic acid. LPP was found to regulate the Nrf2/HO-1 signaling pathway through 8 active substances to protect HaCaT cells against oxidative stress in vitro.